Gene doping: A review of performance-enhancing genetics - Gaffney, G. R.; Parisotto, R. (Pediatric Clinics of North America, 2007)
Unethical athletes and their mentors have long arrogated scientific and medical advances to enhance athletic performance, thus gaining a dishonest competitive advantage. Building on advances in genetics, a new threat arises from athletes using gene therapy techniques in the same manner that some abused performance-enhancing drugs were used. Gene doping, as this is known, may produce spectacular physiologic alterations to dramatically enhance athletic abilities or physical appearance. Furthermore, gene doping may present pernicious problems for the regulatory agencies and investigatory laboratories that are entrusted to keep sporting events fair and ethical. Performance-enhanced genetics will likewise present unique challenges to physicians in many spheres of their practice.